PENGARUH LABEL HALAL DAN DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK WARDAH - Regita Cahyani; David C.E Lisapaly; La Ode Hamida (STIE ENAM ENAM KENDARI, 2022)
This research aims to know the impact of halal labels and digital marketing on purchasing decisions for Wardah cosmetic products in students of the management study program of sekolah tinggi ilmu ekonomi enam enam kendari. This research is quantitative descriptive. The data of this study were obtained through observation, interviews and questionnaires. The data analysis method used is descriptive analysis by processing the data from the questionnaire through SPSS. Based on the results of research on the effect of halal labels and digital marketing on purchasing decisions for Wardah cosmetic products, it can be concluded that it means that the two variables, namely the halal label (XI) and digital marketing (X2) together (simultaneously) have a positive and significant effect on the purchasing decision variable ( Y) in students of the management study program at sekolah tinggi ilmu ekonomi enam enam kendari. Based on the test results on the halal label variable, it partially has a positive and significant effect on the purchasing decision variables in the management study program of sekolah tinggi ilmu ekonomi enam enam kendari and based on the test results on the digital marketing variable, it partially has a positive and significant effect on purchasing decisions for the student of the study program management of sekolah tinggi ilmu ekonomi enam enam kendari.